Insights into the molecular evolution of oxytocin receptor ligand binding. (29th January 2013) - Koehbach, Johannes; Stockner, Thomas; Bergmayr, Christian; Muttenthaler, Markus; Gruber, Christian W.
Abstract : The design and development of selective ligands for the human OT (oxytocin) and AVP (arginine vasopressin) receptors is a big challenge since the different receptor subtypes and their native peptide ligands display great similarity. Detailed understanding of the mechanism of OT's interaction with its receptor is important and may assist in the ligand- or structure-based design of selective and potent ligands. In the present article, we compared 69 OT- and OT-like receptor sequences with regards to their molecular evolution and diversity, utilized an in silico approach to map the common ligand interaction sites of recently published G-protein-coupled receptor structures to a model of the human OTR (OT receptor) and compared these interacting residues within a selection of different OTR sequences. Our analysis suggests the existence of a binding site for OT peptides within the common transmembrane core region of the receptor, but it appears extremely difficult to identify receptor or ligand residues that could explain the selectivity of OT to its receptors. We remain confident that the presented evolutionary overview and modelling approach will aid interpretation of forthcoming OTR crystal structures.